Strategi Peningkatan Pariwisata Sengon Hills melalui Pengembangan Fasilitas dan Promosi Wisata Berkelanjutan - Hidayatullah, Elit Ave; Hanifa, Hanifa Dyanti Anjani; Aqila, Shindidah Lady; Prasasti, Aura; Rohaniwati; Aulia, Nissa; Ummisah, Siti; Aulia, Shindy; Azzahra, Veronica; Orchidea, Nabila; Nada, Alifa (Jurnal Abdimas Pariwisata, 2024)
The Strategy for Enhancing Tourism in Sengon Hills Through the Development of Facilities and Sustainable Tourism Promotion The real work lecture (KKN) activity in Girimulyo village, Girimulyo hamlet aims to improve the quality of Sengon Hill, which is a swimming pool tour in Girimulyo hamlet, through the development of facilities and sustainable tourism promotion. This KKN activity was carried out with the stages of field observation methods, interviews with BUMDes (Village-Owned Enterprises) administrators, discussions and documentation, this activity involved 10 KKN group members in Girimulyo hamlet. The result of this activity is the formation of a Sengon Edu Play ground which consists of playing while learning media in the form of snakes and ladders and puzzles. The next result is a website and tourist location plan which is one form of development of Sengon Hill tourism promotion that facilitates the spread of promotion in the form of Sengon Hill tourism information and attracts the attention of visitors in the form of visualization seen by tourists related to information from the website and unique tourist location plan.The making of Sengon Edu Play ground in Sengon Hill tourism aims to eliminate boredom in learning by learning while playing will be a solution to eliminate children's boredom in learning.